A study of childhood cancer survivors' engagement with long-term follow-up care: 'To attend or not to attend, that is the question'. (April 2020) - Knighting, Katherine; Kirton, Jennifer A.; Thorp, Nicola; Hayden, James; Appleton, Lynda; Bray, Lucy
Abstract: Purpose: In the UK, there are over 40, 000 childhood cancer survivors (CCS); this figure grows approximately 1300 annually. Two-thirds are at risk of developing serious disabling or life-threatening conditions due to adverse late effects of the cancer or treatment received in childhood. Life-long, follow-up care for the surveillance and management of late effects is recommended. This study explored CCS' views and experiences of long-term follow-up (LTFU) care within a cancer centre. Methods: Paper questionnaires (n = 113) and qualitative interviews (n = 13). Results: The majority (n = 83, 80%) of CCS reported being satisfied with their LTFU care and felt that it was important to attend long-term survivorship follow-up (n = 97, 86%). However, some were not well informed about their cancer treatment history, purpose for attending the clinic or the potential for late effects. Barriers associated with LTFU included; provision of information, lack of interpersonal relationships, practical and logistic challenges. Conclusions: Barriers identified can be addressed through strategies including provision of verbal and written information and care plans to increase CCS' knowledge of their cancer history, risk of late effects and the purpose of LTFU care, both at transition and throughout their survivorship journey; patient-centred services that enhance patient choice and flexibility of access to multiple specialities; and use of risk stratified pathways to encourage supported self-management based on cancer type, co-morbidity, and level of professional involvement required. Improving regular provision of information at critical time-points, and exploring a flexible, patient-centred delivery of LFTU care based on risk, could increase attendance and self-management in CCS. Highlights: What is known? Two-thirds of childhood cancer survivors (CCS) are at risk of developing serious disabling or life-threatening conditions due to adverse late effects of the cancer or treatment received. Long-term, follow-up care (LTFU) for surveillance and management of late effects is recommended but internationally take up is low. What does this study add? Engagement in LTFU was affected by CCS′ not being well informed about their treatment history, purpose for attending the clinic or potential for late effects, lack of interpersonal relationships, practical and logistic challenges. Engagement can be improved with improved provision of information; flexible services with access to multiple specialities; risk stratified pathways to encourage self-management based on cancer type, co-morbidity, and level of professional involvement required.